Pengaruh Teknologi Informasi, Kualitas Pelayanan, Dan Motif Religius Terhadap Kepuasan Nasabah PT. Bank Syariah Mandiri Di Banda Aceh - Zainul, Zaida Rizqi; Ayumiati, Ayumiati; Zakia, Yunda (Universitas Islam Negeri Sunan Kudus, 2020)
This study aims to determine what factors influence information technology, service quality, and religious motives on customer satisfaction at PT BSM Banda Aceh. In this study the number of samples studied was 91 customers, the determination of which was done using Probability Random Sampling. The research method used is quantitative with data collection techniques using a questionnaire as an instrument for collecting data. Data analyzed uses validity and reliability to evaluate the questionnaire. The results of the study indicate that information technology, service quality, and religious motives jointly influence customer satisfaction. This can be seen by looking at the acquisition of F test results, where Sig is 0,000 <0.05 and F count is 138.615> from F table 2.71. So that H0 is rejected and Ha is accepted, it can be concluded that simultaneously (simultaneously) information technology variables, service quality, and religious motives have a positive and significant effect on customer satisfaction.